Design and Construction of a Web-Based Work Permit and Leave Application Information System for CV. Dodi Brothers - Nessa Marshanda; Suhartini; Jepri Yandi (Yayasan Kita Menulis, 2026)
CV Company. Dodi Brothers is a private company engaged in the procurement of goods and services. At this time the company CV. Dodi Brothers does not yet have a website for applying for work permits and leave, so the aim of this research is to make it easier for employees to apply for work permits and leave, and to make it easier for admins to approve work permit and leave applications submitted by employees. The research method uses a qualitative descriptive method with data collection techniques in the form of observation, interviews and literature study, data sources consist of primary and secondary. Meanwhile, the method for system development used is the RAD (Rappid Application Development) method. The system design tool used is UML (Unified Modeling Language). This website is designed using the PHP (Hypertext Processor) programming language. MySQL database and coding using Visual Studio Code.